2015
DOI: 10.1530/eje-15-0036
|View full text |Cite
|
Sign up to set email alerts
|

The 10 Hounsfield units unenhanced computed tomography attenuation threshold does not apply to cortisol secreting adrenocortical adenomas

Abstract: Context: Computed tomography (CT) unenhanced attenuation value of !10 Hounsfield units (HU) has an excellent specificity (98%) to diagnose lipid-rich adrenocortical adenomas (ACAs) with a weaker sensitivity (71%). Objective: To determine from a routine clinical perspective if unenhanced attenuation value is influenced by cortisol secretion in ACAs. Design: This was a retrospective study of cases collected between 2009 and 2012. Setting: This study was conducted in a tertiary-care university hospital. Patients:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
5
16
1
Order By: Relevance
“…Our results are in line with two previous CT studies in patients with CS demonstrating an inverse linear relationship between precontrast CT attenuation level and the percentage of lipid‐rich cells . Taken together, our data support the concept that cortisol hypersecretion by an adrenal adenoma may be associated with distinctive radiological characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with two previous CT studies in patients with CS demonstrating an inverse linear relationship between precontrast CT attenuation level and the percentage of lipid‐rich cells . Taken together, our data support the concept that cortisol hypersecretion by an adrenal adenoma may be associated with distinctive radiological characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…The utilization of imaging parameters for the prediction of the functionality and particularly the cortisol excess has been investigated in very few studies. Chambre and colleagues reported that the unenhanced attenuation value of CT had very poor sensitivity to diagnose adrenal cortical adenomas (ACA) in patients with CS . The study by Mosconi and colleagues showed that an adrenal protocol CT scan could predict autonomous cortisol secretion from an AI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes have allowed surgical treatment for most atypical benign tumours to be ruled out, that is, poor lipid nonfunctioning adenomas with atypical features on CT scan. These non‐secreting undetermined adrenal masses with spontaneous densities higher than 10 Hounsfield unit (HU), as indicated by CT scan, have been extensively studied . There are several benign imaging findings that rule out the presence of malignancy with excellent negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…There are several benign imaging findings that rule out the presence of malignancy with excellent negative predictive value. These include the following: (i) spontaneous density less than 10 HU on unenhanced CT scan followed with relative or absolute washout measurement greater than 40% or 60% on contrast‐enhanced CT scan; (ii) chemical shift MRI with a decrease of signal intensity greater than 20% between in‐ and opposed‐phase images; and (iii) an adrenal‐to‐liver standard uptake value less than 1.45 on 18 F‐fluorodeoxyglucose PET . Surgery is still required in patients with indeterminate adrenal masses, especially when patients have a long projected life expectancy, because of the risks of tumour growth and hormonal oversecretion development.…”
Section: Discussionmentioning
confidence: 99%